2018
DOI: 10.1177/0020764018784616
|View full text |Cite
|
Sign up to set email alerts
|

The impact of motives for Facebook use on Facebook addiction among ordinary users in Jordan

Abstract: Among these six motives, escapism and passing time, exhibitionism and companionship, and relationships maintenance were the strong predictors of Facebook addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Communication is an important aspect regarding the use of those applications as well as further factors such as experiencing connectedness, the need to belong, self-presentation, and entertainment or procrastination [6,15]. Guedes et al [16] showed that usage motives such as relationship maintenance, passing time, and entertainment are related to an addictive use, which is in line with other research [17][18][19][20][21]. The definition as well as the main usage motives highlight the relevance of social connectedness, social cognitions, and/or social deficits as important factors involved in the development and maintenance of a social networks use disorder.…”
Section: Introductionsupporting
confidence: 64%
“…Communication is an important aspect regarding the use of those applications as well as further factors such as experiencing connectedness, the need to belong, self-presentation, and entertainment or procrastination [6,15]. Guedes et al [16] showed that usage motives such as relationship maintenance, passing time, and entertainment are related to an addictive use, which is in line with other research [17][18][19][20][21]. The definition as well as the main usage motives highlight the relevance of social connectedness, social cognitions, and/or social deficits as important factors involved in the development and maintenance of a social networks use disorder.…”
Section: Introductionsupporting
confidence: 64%
“…In another study, the prevalence rate among high school students in Thailand was reported as being 41.8% using a cutoff score of 12 or more in the Thai-BFAS (Khumsri et al, 2015). In Jordan, 38.5% of university students classed as being at risk of FA using the BFAS, although no cutoff score was mentioned (Alzougool, 2018). Finally, a study of Malaysian students reported an FA prevalence rate of 47% based on polythetic scoring of the BFAS (Jafarkarimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of FA has been wide-ranging (up to 47% in some cases) but almost all studies have used different criteria and methods of assessing FA (e.g., Alzougool, 2018;Jafarkarimi, Sim, Saadatdoost, & Hee, 2016;Masthi, Cadabam, & Sonakshi, 2015;Khumsri et al, 2015;Shettar, Karkal, Kakunje, Mendonsa, & Chandran, 2017;Wolniczak et al, 2013) and typically using non-representative samples.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Internet-usage time, communication accounted for the largest share, followed by entertainment and games, whereby the most frequently used communication applications were WhatsApp, Instagram, and Snapchat [8]. Communicating and staying in contact with others is generally an important motive for using social networks, as highlighted by several authors [10][11][12][13][14][15]. Following Pertegal, Oliva, and Rodríguez-Meirinhos [16], research also identified two important motives for very young individuals: on the one hand obtaining social recognition, and on the other hand belonging to an online community.Besides several advantages of such applications, research has also critically pointed out that the use of social networks can have undesired and disadvantageous consequences as well.…”
mentioning
confidence: 99%